Effect of LY2109761 on TGF-β1/TGFβRI/Smad Pathway and Hepatic Fibrosis Cysts Formation in Rats Infected with Echinococcus granulosus: an In Vitro and In Vivo Study - Shaohua Zhai; Yueqi Yang; Meihe Hu; Yang Zhou; Yanshuang Yang; Nijun Zou (Acta Parasitologica, 2026)

Fish type I and type II interferons: composition, receptor usage, production and function - Zhen Gan; Shan Nan Chen; Bei Huang; Jun Zou; Pin Nie (Reviews in Aquaculture, 2020)
Interferons ( IFN s) have been reported in vertebrates from fish to mammals. To date, two types of IFN s, i.e. type I and type II IFN s have been reported in a range of fish species in aquaculture. In fish, type I IFN s are clarified into group I and group II , with two cysteines and four cysteines, and further into subgroups a, d, e, h, and b, c, f, respectively. Group I IFN s appear to exist in all fish species, whereas group II IFN s are discovered only in certain species such as cyprinids, salmonids and perciform fish. It seems preferentially functional that group I IFN s signal through cytokine receptor family B ( CRFB ) 5 and CRFB 1, while group II IFN s through CRFB 5 and CRFB 2. But they all initiate a same signalling pathway for the expression of interferon induced genes. The information about the production and the function of type I IFN s in fish are further summarized in the review. Interestingly, two members of type II IFN s, IFN ‐γ and a unique member, IFN ‐γ related gene ( IFN ‐γrel) exist in fish, and IFN ‐γ and IFN ‐γrel can separately become homodimers for signalling through CRFB 13, CRFB 17, CRFB 6 and CRFB 17, respectively. In addition, the variation in the composition of type I and type II IFN s as well as in their receptors in some cyprinid and salmonid fish has also been reviewed. It is suggested that future perspectives for the research on type I and type II IFN s in fish are outlined from a comparative and evolutionary point of view.

An improved method for in vitro culture of glochidia in freshwater mussel Cristaria plicata (Mollusca, Bivalvia) - Xue-Yan Ma; Hai-Bo Wen; Jun Zou; Wu Jin; Dan Hua; Ruo-Bo Gu; Pao Xu (Hydrobiologia, 2018)